Gastrointestinal Bleeding in Patients With New Coronavirus Infection COVID-19 - V. D. Anosov; S. A. Domrachev; S. V. Ovchinnikov; N. O. Solovyov (Неотложная медицинская помощь, 2023)
Currently, the issue of coronavirus infection COVID-19 remains extremely relevant, and the SARS-CoV-2 virus also affects the gastrointestinal tract, and in some cases, coronavirus infection can be complicated by gastrointestinal bleeding. Up to 13% of COVID-19 patients have this complication. At the same time, the issue of determining risk factors for the development of gastrointestinal bleeding in patients with COVID-19 remains unresolved in the world literature. There is no single standardized approach to the treatment of gastrointestinal bleeding in patients with COVID-19. The above reasons served as prerequisites for this literature review. The purpose of the literature review is to establish risk factors and groups for gastrointestinal bleeding in patients with a new coronavirus infection, and to determine current and effective methods of treating this disease.